Pengaruh Iklim Organisasi, Etoskerja Dan Disiplin Kerja Terhadapefektivitas Kerja Karyawan Pada PT. Telekomunikasi Indonesia Tbk Cabang Tenggarong - Hermanto, Muhammad (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2015)
Problems that researchers look at PT. Telkom Tenggarong Branch is the level of employee effectiveness is still not optimal. Particularly visible from the factors that cause in terms of a less conducive working climate, minimal work ethic and lack of running and frequent discipline of work. This is seen with the lack of initiative, awareness and responsibility of employees to the work, often delaying the work given from the employer so that work can not be completed on time, lack of cooperation in handling the job and many employees who do not work and are less obedient and Obedient to working hoursThis study uses quantitative data obtained from questionnaire data. The number of research samples are 25 people with the method of taking by census. The analytical tool used multiple linear regression analysis with hypothesis testing using F test and t test.The result of F test calculation obtained F count is 45,343, while the value of F table obtained value of 2.76 this means that (Fhitung 45, 343> Ftabel 2.76) with significant value <0,05, so can be said organization climate variable, Work ethic and work discipline simultaneously able to show its effect on work effectiveness. Then the first hypothesis is accepted. From the three t test results above shows the partial correlation value of variable discipline of work is greatest compared to organizational climate variables and work ethic that is equal to 0.612 or 61.2%, so that the work discipline variable is the most dominant variable affecting the effectiveness of employees at PT. Telekomunikasi Indonesia Tbk Tenggarong Branch. From the description, it can be concluded that the second hypothesis is accepted Keywords: Organizational Climate, Work Ethic, Work Discipline, Work Effectiveness.